Extraordinary electrocatalytic performance for formic acid oxidation by the synergistic effect of Pt and Au on carbon black. (June 2018) - Fan, Hongsheng; Cheng, Ming; Wang, Lei; Song, Yuanjun; Cui, Yimin; Wang, Rongming
Abstract: Improving catalyst performance and understanding reaction mechanism of formic acid electrooxidation (FAO), a typical anodic reaction in fuel cells, are of technological and scientific importance. Here, Pt-Au/C catalysts were designed and synthesized for catalyzing the FAO reaction. An ultrasound-assisted method was developed to enable the uniform and dense loading of Pt and Au on carbon black without any surfactant. The Pt-Au/C sample with a Pt/Au atomic ratio of 32:68 exhibits an FAO catalytic activity of 14.5 A mgPt −1, which is 153 times higher than that of Pt/C. The extraordinary performance is attributed to the optimized synergistic effect of Pt and Au. Density functional theory calculations disclose that the neighboring Au decreases the reaction energy barriers of the direct pathway on Pt. This work demonstrates a promising FAO catalyst and an effective strategy to obtain supported catalysts. Graphical abstract: fx1 Highlights: An ultrasound-assisted strategy was developed to synthesize Pt-Au/C catalysts. Pt and Au nanoparticles were uniformly and densely loaded on carbon black without any surfactant. The Pt-Au/C-3 sample exhibited a 153 times higher activity than Pt/C in catalyzing formic acid oxidation. DFT calculations confirmed the promoting effect of neighboring Au.